Pelatihan Perpajakan Siswa SMK Kartini Surabaya - Rudi Pratono; Soemaryono Soemaryono (Universitas Kristen Indonesia Toraja, 2024)
The aim of this community service activity is to increase insight and develop knowledge about taxation for students at SMK Kartini Surabaya. As well as providing students with knowledge in income tax skills, especially income tax for individual taxpayers. The training participants were 55 students from Kartini Vocational School, Surabaya, Accounting Study Program. The method of implementing community service activities is carried out by providing theoretical and practical knowledge material for calculating income tax for individual taxpayers in accordance with the tax regulations currently in force. Starting from understanding the meaning of tax object, tax subject, taxpayer as well as the meaning of income tax, individual taxpayer tax rates and how to report income tax. The results achieved in this activity are that the participants or students are able to understand the practice of calculating income tax for individual taxpayers in a fundamental way that applies in Indonesia and are able to understand the rules regarding non-taxable income limits and the amount of income that does not have to pay income tax for individual taxpayers. able to understand the procedures for creating billing codes for tax deposits and able to understand the procedures for reporting personal income tax every month and annual reports.